Resíduos madeireiros da indústria ervateira para produção de painéis MDP - Souza, Joel Telles de (2016)
MDP (Medium Density Particleborad) boards have been developed in order to provide options for the use of waste produced by logging activity. It has the wooden particle board as a precursor. It can be considered an evolution of the particle board in terms of production process and quality of final product. The current study aims at assessing the use feasibility of wood waste of the mate tea (Ilex paraguariensis A. St. Hil.) industrialization, for MDP boards manufacture, combining different proportions of wood of Eucalyptus grandis and Pinus elliottii, glued with urea-formaldehyde. In order to carry out this study, wood waste of mate tea from Barão de Cotegipe – RS and wood particles of pine and eucalyptus from forest planting felling cycle of the Federal University of Santa Maria (UFSM) have been used. All production process of MDP boards occurred at the Laboratory of Forest Products of the UFSM, whereas the physical tests of water absorption (WA), swelling in thickness (ST), mechanical tests of elasticity module (EMO) and rupture module (RMO) of static bending, screws pulling (SP), perpendicular traction to the board surface (PT) and surface resistance (SR) occurred at the Duratex laboratory in Taquari RS. Nondestructive tests of ultrasound and colorimetry have been carried out at the Wood Industrial Engineering, Federal University of Pelotas (UFPel). At the different layers of MDP boards, particles from the outer layer (OL) had an average slenderness coefficient very similar for the three species analyzed, whereas to the inner layer (IL), where the particles are bigger, the same similarity appeared for pine and eucalyptus, for mate tea, though, this coefficient was low. The average apparent density (AP) and equilibrium moisture content of the boards produced have not significantly varied with 5% of error probability. Modeling of mixtures showed that WA and ST are determined by quadratic models, as for 2 hours as for 24 hours of immersion. In the mechanical properties, modeling presented itself in the following way: RMO of static bending, SP and PT are determined by the linear model, whereas EMO of static bending and SR are determined by the quadratic model. The density profiles of the MDP boards had a behavior similar to what happens in the commercial MDP, with high values of AD in the OL and lower values in the IL. This proceeding happened gradually between the layers. The nondestructive assessment method using ultrasound can be used in predicting the physical properties of MDP boards and mechanical properties of static bending. Ultimately, colorimetry presented a pinkish coloration for eucalyptus boards and a yellowish coloration for boards produced with pine and mate tea. Thus, we concluded that mate tea wood waste combined with the species commonly used in commercial boards, pine and eucalyptus, can be used in MDP boards without affecting their quality. The use of nondestructive methods collaborated meaningfully for answering the questions of the current study.